The media text as a powerful instrument of mass media - Zhuldyz B. Kurmambayeva, Shattygul L. Yerhozhina, Kalbike U. Yessenova, Zhanalik K. Baltabayeva, Gulbanu S. Kossymova (Opción, 2019)
This study investigates media texts that are an important element of the information and communication process realized through mass media via linguistic techniques that are actively used by authors to make a good impression and linguistic means that have a hidden effect on the recipient. As a result, an event in a vast information field, which is created by various types of mass media, can be interpreted differently. As a conclusion, media texts are capable of creating a media-image of reality and are a powerful instrument of mass media.